2017
DOI: 10.1038/eye.2017.109
|View full text |Cite
|
Sign up to set email alerts
|

A novel graft option after pterygium excision: platelet-rich fibrin for conjunctivoplasty

Abstract: PurposeTo compare the surgical results, complications, and recurrence rates of primary pterygium excision with conjunctival autografts (CA) vs platelet-rich fibrin (PRF) grafts.Patients and methodsA total of 35 eyes of 35 patients with primary pterygium were included in the study. The patients underwent excision of pterygium followed by closure of the bare sclera by CA (group 1, n=20) vs PRF grafts (group 2, n=15). The PRF was generated from the patients' own whole-blood sample by centrifugation and pressing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 27 publications
0
28
3
3
Order By: Relevance
“…Blurred vision or decreased visual acuity, cosmetic problems, chronic inflammation, and irritative symptoms are indications for pterygium surgery. Although degenerated tissue is surgically removed, recurrence may occur [3].…”
Section: Introductionmentioning
confidence: 99%
“…Blurred vision or decreased visual acuity, cosmetic problems, chronic inflammation, and irritative symptoms are indications for pterygium surgery. Although degenerated tissue is surgically removed, recurrence may occur [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cerrahi olarak dejeneratif doku çıkartılmasına rağmen cerrahi sonrası nüks söz konusu olabilmektedir (7). Günümüzde pterjium cerrahisinde birçok yöntem kullanılmasına rağmen en sık kullanılan ve nispeten az nüks görülen yöntem; otolog limbal-konjonktival greft transplantasyonudur (6)(7)(8). Pterjium ameliyatı, erken dönemde yapılırsa gerek anatomik gerekse fonksiyonel başarı artmakta, nüks oranları azalmaktadır (7,8).…”
Section: Introductionunclassified
“…Günümüzde pterjium cerrahisinde birçok yöntem kullanılmasına rağmen en sık kullanılan ve nispeten az nüks görülen yöntem; otolog limbal-konjonktival greft transplantasyonudur (6)(7)(8). Pterjium ameliyatı, erken dönemde yapılırsa gerek anatomik gerekse fonksiyonel başarı artmakta, nüks oranları azalmaktadır (7,8). Çalışmamızın amacı pterjiumu olan hastalarda ameliyat zamanını geciktiren hasta kaynaklı sebepleri, demografik faktörleri bulmak ve sebebe yönelik alınabilecek önlemleri tespit etmektir.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…6 A study reported on the application of PRF in pterygium surgery; however, it only compared PRF grafts with CA. 11 Considering the enrolled sample size and follow-up time, further studies and research need to be undertaken to arrive at a firm conclusion on the efficacy and safety of PRF in pterygium surgery.…”
mentioning
confidence: 99%